Alcohol‐Associated Liver Disease Before and After COVID‐19—An Overview and Call for Ongoing Investigation. Issue 9 (5th June 2021) - Moon, Andrew M.; Curtis, Brenda; Mandrekar, Pranoti; Singal, Ashwani K.; Verna, Elizabeth C.; Fix, Oren K.
Abstract : The Coronavirus Disease 2019 (COVID‐19) pandemic has exacted a heavy toll on patients with alcohol‐associated liver disease (ALD) and alcohol use disorder (AUD). The collective burden of ALD and AUD was large and growing, even before the COVID‐19 pandemic. There is accumulating evidence that this pandemic has had a large direct effect on these patients and is likely to produce indirect effects through delays in care, psychological strain, and increased alcohol use. Now a year into the pandemic, it is important that clinicians fully understand the effects of the COVID‐19 pandemic on patients with ALD and AUD. To fill existing gaps in knowledge, the scientific community must set research priorities for patients with ALD regarding their risk of COVID‐19, prevention/treatment of COVID‐19, changes in alcohol use during the pandemic, best use of AUD treatments in the COVID‐19 era, and downstream effects of this pandemic on ALD. Conclusion: The COVID‐19 pandemic has already inflicted disproportionate harms on patients with ALD, and ongoing, focused research efforts will be critical to better understand the direct and collateral effects of this pandemic on ALD. Abstract : COVID‐19 has inflicted disproportionate direct and indirect harms on patients with alcohol‐associated liver disease. Ongoing research efforts will be critical to better understand the effects of this pandemic on patients with alcohol‐associated liver disease.image